ANALISIS PENGGUNAAN METODE COOPERATIVE LEARNING TERHADAP PERMASALAHAN MEMBACA MENULIS PERMULAAN (MMP) SISWA KELAS III - Hani Zakiyatun Nisa; Siti Ikromah; Fikri Irmansyah; Ujang Jamaludin; Sigit Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study discusses the use of the cooperative learning model for beginning reading and writing problems (MMP) in class III at SDN Sindangraksa, located in Serang City. This research uses a descriptive qualitative approach with a case study technique. The purpose of this study was to see the effectiveness of the cooperative learning method for students with low initial reading and writing abilities. Based on the results of observations and interviews, the problem that occurs is that there are still students who are not fluent in reading and writing at the beginning of class III. The main factors of these problems are the lack of motivation to learn, the existence of family environmental factors and the use of inappropriate learning methods. Therefore, researchers took direct action using the cooperative learning method in an effort to help students who were still low in reading and writing skills in understanding the material. Cooperative learning method is a method by grouping students in learning activities. Based on the results of the research conducted, it can be concluded that the use of the cooperative learning method is effective and has a fairly good impact on students who are still low in their reading and writing abilities.